2016
DOI: 10.1136/bmjopen-2015-009196
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical prediction rule to improve peripheral intravenous cannulae first attempt success in the emergency department and reduce post insertion failure rates: the Vascular Access Decisions in the Emergency Room (VADER) study protocol

Abstract: IntroductionPeripheral intravenous cannula (PIVC) insertion is one of the most common clinical interventions performed in emergency care worldwide. However, factors associated with successful PIVC placement and maintenance are not well understood. This study seeks to determine the predictors of first time PIVC insertion success in emergency department (ED) and identify the rationale for removal of the ED inserted PIVC in patients admitted to the hospital ward. Reducing failed insertion attempts and improving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 71 publications
3
45
1
7
Order By: Relevance
“…Peripheral intravenous cannulation is one of the most commonly performed invasive procedures in the emergency department (ED) . Peripheral intravenous cannulas (PIVCs) are intended for the delivery of fluid, medication, blood, or contrast during the patient's hospital stay.…”
mentioning
confidence: 99%
“…Peripheral intravenous cannulation is one of the most commonly performed invasive procedures in the emergency department (ED) . Peripheral intravenous cannulas (PIVCs) are intended for the delivery of fluid, medication, blood, or contrast during the patient's hospital stay.…”
mentioning
confidence: 99%
“…Nurses in this area frequently encounter patients affected by different conditions and comorbidities, such as oedema, hypovolaemia or dehydration, lymphadenectomy and chemotherapy previously administered through PIVC that could lead to repeated attempts to place a PIVC, pain and delays in obtaining the care required (Guillon et al, ; Witting, ). In contrast, previous research identified as risk factors for difficult cannulation in emergency only age, BMI, drug abuse, sickle cell disease (Carr, Rippey, Cooke, et al, ) and diabetes (Fields et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…The literature search found ten studies investigating 21 patient risk factors, including age, gender, race, weight/BMI, medical diseases and conditions (such as diabetes, cancer, lymphadenectomy, previous chemotherapy or radiotherapy, oedema, parenteral drug abuse) (Armenteros‐Yeguas et al, ; Bensghir et al, ; Carr, Rippey, Cooke, et al, ; Fields, Piela, Au, & Ku, ; Jacobson & Winslow, ; Juvin, Blarel, Bruno, & Desmonts, ; Lapostolle et al, ; Van Loon, Puijn, Houterman, & Bouwman, ; Piredda et al, ; Sebbane et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral intravenous cannulation (PIVC) is a very commonly performed procedure in the emergency department (ED) . Currently there are no standardized guidelines or indications outlining when a PIVC should be inserted in an emergency setting .…”
Section: Introductionmentioning
confidence: 99%